(untitled) (International journal of artificial intelligence, 2025)
In order to convincingly and artistically depict the unique, distinctive life path of Sufi saints, creators use various means. In this, special importance is also paid to express their differences from ordinary people. Based on this goal, the writer can use non-existent images. Tolqin Hayit also introduces the image of the Spirit Bird, which is invisible to all people in real life, in his artistic interpretation of the personality of Bahauddin Naqshband in “Bahadin Naqshband or the Story of the Buraq Valley”. This article discusses the role of the Spirit Bird in the content and idea of ​​the work, as well as its importance in illuminating Bahauddin’s inner world.